Application of singular value decomposition analysis to time‐dependent powder diffraction data of an in‐situ photodimerization reaction. (2nd April 2014) - Mabied, Ahmed F.; Nozawa, Shunsuke; Hoshino, Manabu; Tomita, Ayana; Sato, Tokushi; Adachi, Shin‐ichi
<x xml:space="preserve">Abstract</x> Singular value decomposition (SVD) analysis has important applications for time‐dependent crystallographic data, extracting significant information. Herein, a successful application of SVD analysis of time‐resolved powder diffraction data over the course of an in‐situ photodimerization reaction of anthracene derivatives is introduced. SVD revealed significant results in the case of 9‐methylanthracene and 1‐chloroanthracene. The results support the formation of the 9‐methylanthracene stable dimer phase and suggest the existence of an excimer state.